On estimation of extremal entries of the principal eigenvector of a graph - Prohelika Das; Bipanchy Buzarbarua (AKCE International Journal of Graphs and Combinatorics)
Let [Formula: see text] be the principal eigenvector corresponding to the spectral radius [Formula: see text] of a graph G of order n. In this paper, we find some bounds on the ratio of the maximal component [Formula: see text] to the minimal component [Formula: see text] of the principal eigenvector X in terms of the graph parameters such as the independence number [Formula: see text], the minimum vertex cover number of the vertex [Formula: see text] and the chromatic number [Formula: see text]. Also, we present some bounds on the extremal component [Formula: see text] of the principal eigenvector X. An upper bound of the spectral radius [Formula: see text] of G in terms of the minimum vertex cover number [Formula: see text] and order of the graph n is also introduced in this paper.